COMPACT SWITCHED CAPACITOR CONVERTERS FOR ENHANCED STEPUP MULTILEVEL INVERTER DESIGNS - Rao Paddam, Babu; Sirisaiah, Lella; Nandini, P. (International Journal of Psychosocial Rehabilitation, 2019)
This work presents the first proposed basic cell (BC) of a novel switched capacitor converter (SCC). The proposed SCC’s generalised structure is then developed after that. Compared to previous recently produced SCCs, the developed SCC requires less switches, drivers, diodes, capacitors, and conducting switches in the current flow channels and capacitor charging paths. The next development is a switched capacitor multilevel inverter (SCMLI) that makes use of two generalised SCCs. In addition, a cascaded extension of the suggested SCMLI is implemented and examined for both symmetric and asymmetric DC source arrangements. A thorough examination of the best capacitance option for 13 level SCMLI switching capacitors is provided. A thorough comparative analysis reveals that, in comparison to existing SCMLIs, the suggested SCMLI requires less components. In addition, compared to the other SCMLIs, the suggested structure has the lowest cost function per level per boosting factor. The benefits and efficacy of the suggested structure are validated by presenting extensive experimental findings that take into account the fundamental switching frequency scheme. Index Table of Contents: This study presents the first proposed basic cell (BC) of a novel switched capacitor converter (SCC). The proposed SCC’s generalised structure is then developed after that. Compared to previous recently produced SCCs, the developed SCC requires less switches, drivers, diodes, capacitors, and conducting switches in the current flow channels and capacitor charging paths. The next development is a switched capacitor multilevel inverter (SCMLI) that makes use of two generalised SCCs. In addition, a cascaded extension of the suggested SCMLI is implemented and examined for both symmetric and asymmetric DC source arrangements. A thorough examination of the best capacitance option for 13 level SCMLI switching capacitors is provided. A thorough comparative analysis reveals that, in comparison to existing SCMLIs, the suggested SCMLI requires less components. In addition, compared to the other SCMLIs, the suggested structure has the lowest cost function per level per boosting factor. The benefits and efficacy of the suggested structure are validated by presenting extensive experimental findings that take into account the fundamental switching frequency scheme. Index Terms: voltage balance, reduced devices, switched capacitor, multilayer inverter, and boosting factor